Observation of replica symmetry breaking in filamentation and multifilamentation - Siqueira André C. A.; Palacios G.; Bautista Jessica E. Q.; Amaral Anderson M.; Reyna Albert S.; Falcão-Filho Edilson L.; de Araújo Cid B. (Nanophotonics)
We report the experimental observation and characterization of Replica Symmetry Breaking (RSB) manifestation while analyzing the transverse intensity profile of laser pulses in filamentation experiments using sapphire crystal and distilled water, excited by a femtosecond laser centered at 800 nm. The RSB arises from the competition between self-focusing and plasma defocusing, subject to local fluctuations in the nonlinear refractive index generated by plasma via multiphoton excitation, which subsequently promotes frustration among modes. Our results confirm the existence of glassy-like photonic states not only in multifilamentation, as previously reported [W. Ettoumi, J. Kasparian, and J. Wolf, “Spin-glass model governs laser multiple filamentation,” Phys. Rev. Lett., vol. 115, no. 3, pp. 033902, 2015], but also in the generation of a single filament and in filamentation accompanied by conical emission. These findings improve the understanding of statistical nonlinear optics by establishing connections with magnetism and highlighting the glassy-like behavior of light in the context of ultrafast optical phenomena.